Reconstitution of virus-specific CD4 proliferative responses in pediatric HIV-1 infection. - Feeney, M; Draenert, R; Roosevelt, K; Pelton, S; McIntosh, K; Burchett, S; Mao, C; Walker, B; Goulder, P (2003)
Gag-specific CD4 proliferative responses correlate inversely with HIV-1 RNA levels in infected adults, and robust responses are characteristic of long-term nonprogressive infection. However, strong responses are seldom detected in adult subjects with progressive infection and are not generally reconstituted on highly active antiretroviral therapy (HAART). To date, the role of HIV-1-specific Th responses in children has not been thoroughly examined. We characterized Gag-specific CD4 responses among 35 perinatally infected subjects, including 2 children who spontaneously control viremia without antiretroviral therapy, 21 children with viral loads (VL) of <400 on HAART, and 12 viremic children. Gag-specific Th activity was assessed by lymphoproliferative assay, and responses were mapped using overlapping Gag peptides in an IFN-gamma ELISPOT. Robust proliferative responses were detected in the children exhibiting spontaneous control of viremia, and mapping of targeted Gag regions in one such subject identified multiple epitopes. Among children >or=5 years old, 14 of 17 subjects with VL of <400 on HAART demonstrated a significant p24 proliferative response (median p24 stimulation index, 20), in contrast with only 1 of 9 viremic children (median p24 stimulation index, 2.0; p = 0.0008). However, no subject younger than 5 years of age possessed a significant response, even when viremia was fully suppressed. When compared with adults with VL of <400 on HAART, Th responses among children with VL of <400 were both more frequent (p = 0.009) and of greater magnitude (p = 0.002). These data suggest that children may have a greater intrinsic capacity to reconstitute HIV-1-specific immunity than adults, and may be excellent candidates for immune-based therapies.